The effect of plant diversity on fungus garden development and foraging behavior of leaf-cutting ants (Hymenoptera: Formicidae) - Camargo, Roberto S. [UNESP]; Forti, Luiz Carlos [UNESP]; De Melo Rocha, Mariana [UNESP]; De Matos, Carlos Alberto O. [UNESP]; Lopes, Juliane F. [UNESP]; De Andrade, Ana Paula P. [UNESP]; Verza, Sandra S. [UNESP] (My University, 2003)
The leaf-cutting ants forage a wide variety of plant species, used for symbiotic fungus cultivation. To better understand this tripartite complex interaction, 24 colonies of Acromyrmex subterraneus brunneus were conditioned for 4 months to 6 different plants (Citrus spp., Ligustrum spp., Acalypha spp., Eucalyptus spp., Alchornea triplinervia, Melia spp.), to verify the influence of conditioning on foraging behavior of workers. The effect of plants on symbiotic fungus development was studied separately, through macerated plants in Agar and culture medium A as the control. During foraging, workers presented polyphagic foraging behavior, refusing the plants to which they were conditioned. The selection of plants is not correlated with the plant substrate that promotes good development of symbiotic fungus. Such results demonstrate the importance of plant diversity for fungus garden maintenance.
Keywords: Acromyrmex subterraneus brunneus; Leaf-cutting ant; Plant selection; Symbiont fungus; Acalypha; Acromyrmex; Acromyrmex subterraneus; Alchornea; Atta; Citrus; Eucalyptus; Formicidae; Fungi; Hymenoptera; Ligustrum; Melia; Meliaceae